2023
DOI: 10.1108/aaaj-09-2020-4950
|View full text |Cite
|
Sign up to set email alerts
|

Between consultation and control: how incubators perform a governance function for entrepreneurial firms

Abstract: PurposeThis paper examines the governance function that incubators perform for entrepreneurial firms. The authors demonstrate that this governance function has both a consultative and a control dimension and illustrate how these are enacted in the interactions between incubators and entrepreneurs. The authors also show how these interactions come into being and how entrepreneurs assess the value of the governance role played by incubators.Design/methodology/approachThe paper is based on a cross-sectional inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 63 publications
(183 reference statements)
0
1
0
Order By: Relevance
“…Secondly, the authors found for the first time that the interventions of incubator managers as gatekeepers to incubatees is necessary, and the results of gatekeeper depth intervention are better than breadth intervention. It is known that the incubator is important for the incubatees (Flanschger et al, 2023). This study digs deeper inside incubators, considers managers as gatekeepers, compares gatekeeper's depth intervention with breadth intervention, and finds that the gatekeeper's depth intervention results are better than the breadth intervention.…”
Section: Discussionmentioning
confidence: 98%
“…Secondly, the authors found for the first time that the interventions of incubator managers as gatekeepers to incubatees is necessary, and the results of gatekeeper depth intervention are better than breadth intervention. It is known that the incubator is important for the incubatees (Flanschger et al, 2023). This study digs deeper inside incubators, considers managers as gatekeepers, compares gatekeeper's depth intervention with breadth intervention, and finds that the gatekeeper's depth intervention results are better than the breadth intervention.…”
Section: Discussionmentioning
confidence: 98%